Surface modification by plasma etching impairs early vascularization and tissue incorporation of porous polyethylene (Medpor®) implants. Issue 8 (10th September 2015) - Laschke, Matthias W.; Augustin, Victor A.; Sahin, Fadime; Anschütz, Dieter; Metzger, Wolfgang; Scheuer, Claudia; Bischoff, Markus; Aktas, Cenk; Menger, Michael D.
Abstract: Porous polyethylene (Medpor®) is commonly used in craniofacial reconstructive surgery. Rapid vascularization and tissue incorporation are crucial for the prevention of migration, extrusion, and infection of the biomaterial. Therefore, we analyzed whether surface modification by plasma etching may improve the early tissue response to Medpor®. Medpor® samples were treated in a plasma chamber at low (20 W; LE‐PE) and high energy levels (40 W; HE‐PE). The samples and non‐treated controls were implanted into mouse dorsal skinfold chambers to analyze angiogenesis, inflammation, and granulation tissue formation over 14 days using intravital fluorescence microscopy, histology, and immunohistochemistry. Scanning electron microscopy (SEM) analyses revealed that elevating energy levels of plasma etching progressively increase the oxygen surface content and surface roughness of Medpor®. This did not affect the leukocytic response to the implants. However, LE‐PE and HE‐PE samples exhibited an impaired vascularization. This was associated with a reduced formation of a collagen‐rich granulation tissue at the implantation site. Additional in vitro experiments showed a reduced cell attachment on plasma‐etched Medpor®. Thus, plasma etching may not be recommended to improve the clinical outcome of reconstructive interventions using Medpor®. However, it may be beneficial for temporarily implanted polyethylene‐based biomedical devices for which tissue incorporation is undesirable. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1738–1748, 2016.